Life stage impact on the human skin ecosystem: lipids and the microbial community - Martin P. Pagac; Bala Davient; Luca Antonio Plado; Hilbert Yuen In Lam; Shi Mun Lee; Aarthi Ravikrishnan; Wee Ling Esther Chua; Sneha Muralidharan; Aishwarya Sridharan; Antony S. Irudayaswamy; Ramasamy Srinivas; Stephen Wearne; et al. (npj Biofilms and Microbiomes)
Abstract Sebaceous free fatty acids are metabolized by multiple skin microbes into bioactive lipid mediators termed oxylipins. This study investigated correlations between skin oxylipins and microbes on the superficial skin of pre-pubescent children (N = 36) and adults (N = 100), including pre- (N = 25) and post-menopausal females (N = 25). Lipidomics and metagenomics revealed that Malassezia restricta positively correlated with the oxylipin 9,10-DiHOME on adult skin and negatively correlated with its precursor, 9,10-EpOME, on pre-pubescent skin. Co-culturing Malassezia with keratinocytes demonstrated a link between 9,10-DiHOME and pro-inflammatory cytokines IL-1β and IL-6 production. We also observed strong correlations between other skin oxylipins and microbial taxa, highlighting life stage differences in sebum production and microbial community composition. Our findings imply a complex host-microbe communication system mediated by lipid metabolism occurring on human skin, warranting further research into its role in skin health and disease and paving the way towards novel therapeutic targets and treatments.